1995
DOI: 10.1073/pnas.92.17.7686
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic inhibitor of the mitogen-activated protein kinase cascade.

Abstract: Many diverse extracellular stimuli-including growth factors, hormones, osmolar shock, stress, and elevated temperatureresult in activation of phosphorylation cascades utilizing mitogen-activated protein kinases (MAPKs) (1-8). MAPKs (sometimes called extracellular signal-regulated kinases, or ERKs) comprise a family of related protein kinases that are themselves activated by phosphorylation on threonine and tyrosine residues. The MAPK-activating enzymes (MAPK/ ERK kinases, or MEKs) are unusual in their ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

83
1,724
5
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,583 publications
(1,813 citation statements)
references
References 22 publications
83
1,724
5
1
Order By: Relevance
“…Consistent with this hypothesis, a speci®c (Dudley et al, 1995;Dumont et al, 1998;Lu et al, 1998;Kirken et al, 1997), was found to induce erythroid di erentiation in dose-dependent manners not only in SKT6 cells but also in two other Friend leukemia-derived cell lines, TL200 and 1-2 (Figure 5a,b,c). In these experiments, growth-suppressing e ects of the drug became evident at the concentrations e ective in inducing di erentiation.…”
Section: Mek Inhibitor Pd98059 Induces Erythroid Differentiation In Ssupporting
confidence: 55%
“…Consistent with this hypothesis, a speci®c (Dudley et al, 1995;Dumont et al, 1998;Lu et al, 1998;Kirken et al, 1997), was found to induce erythroid di erentiation in dose-dependent manners not only in SKT6 cells but also in two other Friend leukemia-derived cell lines, TL200 and 1-2 (Figure 5a,b,c). In these experiments, growth-suppressing e ects of the drug became evident at the concentrations e ective in inducing di erentiation.…”
Section: Mek Inhibitor Pd98059 Induces Erythroid Differentiation In Ssupporting
confidence: 55%
“…KDR-mediated signal preferentially modulates DNA synthesis of HUVECs via the activation of ERK1/2. It is generally accepted that the activation of ERK1/2 is required for DNA synthesis (Rousseau et al, 1977;Dudley et al, 1995). This e ect of ERK1/2 is thought to be mediated via the induction of cyclin D1 (Weber et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We tested whether TCR-independent lytic granule exocytosis is also ERK dependent by treating cells with two different inhibitors of ERK signaling, PD 98059 (100 µM) and FR 180204 (100 µM), and measuring their effects on exocytosis by measuring LAMP-1 externalization. PD 98059 blocks the MAPKKs MEK 1/2 that phosphorylate and activate ERK [23], while FR 180204 blocks substrate phosphorylation by ERK by occluding its ATP-binding site [24]. Cells were pretreated with drugs or vehicle for one hour and then stimulated with thapsigargin (TG) in combination with phorbol myristate acetate (PMA) for 50 minutes in the continued presence of drug or vehicle.…”
Section: Tcr-independent Lytic Granule Exocytosis Requires Pkc-dependmentioning
confidence: 99%